La fusión carulla-vivero, ¿creó valor? (2014)
This study aims to determine whether the Carulla-Vivero merger in 2000 generated value. It analyses the concept of value, the case study methodology, the merger itself and its outcome. The result of the merger is assessed under two accepted methodologies: EVA-WACC and historical cash flow. Finally, observations, conclusions and recommendations on the merger are drawn, as well as the relevancy of the case study on management issues.